Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/jacs.2c12767
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Nickel-Catalyzed Selective N-Demethylation of Trialkylamines Using C(sp2)–Bromides as HAT Reagents

Abstract: N-Demethylation of trialkylamines is a useful transformation, but typically requires harsh reaction conditions and stepwise procedures, as well as judicious protection of labile functional groups. Herein we report a mild, catalytic approach for the demethylation of trialkylamines by utilizing photoinduced nickel catalysis wherein C(sp2)–bromides serve as hydrogen-atom transfer (HAT) reagents. This method achieves direct demethylation of trialkylamines with wide functional group compatibility, making it highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Recently, the nickel-mediated photocatalysis has been demonstrated to be an efficient approach to address the challenging and previously inaccessible cross-coupling reactions . However, there is a scarcity of studies on the catalytic reactivities of photoexcited nickel complexes . In 2018, Doyle and co-workers found that photoexcitation of Ni II –aryl halide complexes resulted in the generation of long-lived excited 3 d–d state, suggesting that Ni could be utilized as an alternative metal photocatalyst (Scheme ).…”
mentioning
confidence: 99%
“…Recently, the nickel-mediated photocatalysis has been demonstrated to be an efficient approach to address the challenging and previously inaccessible cross-coupling reactions . However, there is a scarcity of studies on the catalytic reactivities of photoexcited nickel complexes . In 2018, Doyle and co-workers found that photoexcitation of Ni II –aryl halide complexes resulted in the generation of long-lived excited 3 d–d state, suggesting that Ni could be utilized as an alternative metal photocatalyst (Scheme ).…”
mentioning
confidence: 99%
“…The N -demethylation of tertiary amines has been established by several methods, including photochemical transformations as well as Cu, Ru, Pd, and Fe ,, catalysis (Scheme A,B). However, most of these studies are performed primarily with simple substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Disadvantages include the use of expensive and toxic reagents, the number of reaction steps under severe conditions, and hazardous by-products. Some recent reports use metal-catalyzed, [23] photocatalyst-free, [24] anodic oxidation [25] highlighting difficulties and revealing the search for new practical discoveries of Ndemethylation methods.…”
Section: Introductionmentioning
confidence: 99%